Prototype of Web-based project management system - Палагін, О. В.; Субботіна, О. В.; Чаплінський, Ю. П. (Problems of Informatization and Control, 2007)
The prototype the Web - based project management system WebPMS is described. The basic functions and subsystems of such system which allow supporting realization of all phases of life cycle of development and performance of projects are considered. The description of features of the system, software realization and experience of its application are given